Conflict between Farmers and Guanacos (Lama guanicoe cacsilensis): Field Surveys, Remote Sensing, and Interviews Provide Information for Conservation of a Critically Endangered Species in Southern Peru - Hugo Castillo-Doloriert; Daniela Velasquez; Yumi Matsuno; Domingo Hoces; Jane C. Wheeler (Animals, 2024)
The Peruvian guanaco (Lama guanicoe cacsilensis) is classified as being “in critical danger of extinction” by the government. In this study, we evaluate how the conflict between farmers and guanacos in the Susapaya and Estique Districts, Tacna Department (Southern Peru) may represent a threat to their survival. To evaluate the situation, we 1. Conducted field surveys to monitor guanaco presence, 2. Used available remote sensing data to map guanaco movement, and 3. interviewed the impacted farmers concerning their losses. Remote sensing data showed that sedentary guanaco family groups located in prime steppe vegetation habitats never entered agricultural areas, while field surveys showed that bachelor bands and solitary individuals did, perhaps seeking forage due to growing population pressure. Interview data found that 90% of community farmers felt that guanacos were a problem best resolved by better fencing (45%), hunting (19%), or increased security (16%), and 92% saw no value in the conservation of the species. Hunting is illegal, given the critically endangered status of guanacos in Peru, so additional efforts are needed to both educate those who feel guanacos are a menace and involve them in efforts to preserve the species.